2012
DOI: 10.1371/journal.pone.0052701
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Cocaine of Dopamine Receptors through miRNA-133b in Zebrafish Embryos

Abstract: The use of cocaine during pregnancy can affect the mother and indirectly might alter the development of the embryo/foetus. Accordingly, in the present work our aim was to study in vivo (in zebrafish embryos) the effects of cocaine on the expression of dopamine receptors and on miR-133b. These embryos were exposed to cocaine hydrochloride (HCl) at 5 hours post-fertilization (hpf) and were then collected at 8, 16, 24, 48 and 72 hpf to study the expression of dopamine receptors, drd1, drd2a, drd2b and drd3, by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 84 publications
5
17
0
Order By: Relevance
“…These expression changes were accompanied by decreased miR-133b, in both encephalon and in the periphery 191 . It will be interesting to validate these findings in mammalian systems and test whether miR-133b may be a useful biomarker for changes occurring within the developing brain reward circuitry.…”
Section: Epigenetics and Addictionmentioning
confidence: 94%
See 1 more Smart Citation
“…These expression changes were accompanied by decreased miR-133b, in both encephalon and in the periphery 191 . It will be interesting to validate these findings in mammalian systems and test whether miR-133b may be a useful biomarker for changes occurring within the developing brain reward circuitry.…”
Section: Epigenetics and Addictionmentioning
confidence: 94%
“…Prenatal cocaine exposure in zebrafish altered mRNA levels of Drd1 , Drd2a , Drd2b , and Drd3 , Pitx3 , and Th , genes known to be relevant for drug taking behavior 191 . These expression changes were accompanied by decreased miR-133b, in both encephalon and in the periphery 191 .…”
Section: Epigenetics and Addictionmentioning
confidence: 99%
“…Parallel changes of dopamine and serotonin in this model is consistent with extensive cross-talk reported in synaptic signaling (Henstridge et al, 2016). Further, an independent study found this miRNA pathway is altered in another neuropsychiatric disorder, cocaine addiction (Barreto-Valer et al, 2012). Zebrafish embryos were exposed to cocaine followed by gene expression analysis at various developmental timepoints.…”
Section: Mirna-mediated Regulation Of Dopamine Signaling In Neurologimentioning
confidence: 99%
“…In zebrafish, 8 dopamine receptors have been cloned (Barreto-Valer et al 2012): D1-like receptor (Drd1), which shares 71% amino acid identity to humans (Li et al 2007); the D2-like receptors (Drd2a, Drd2b, Drd2c, Drd3, Drd4a, Drd4b, and Drd4rs), which show an amino acid identity with human sequence ranging 56-67% (Boehmler et al 2004(Boehmler et al , 2007.…”
Section: Endocrine-related Cancermentioning
confidence: 99%